(untitled) (Philology, 2019)
In the current article, different psycholinguistic theories are reviewed from both linguistic and didactic points of view. The study then presents the way in which adult students from the Academy of the Ministry of Interior in Sofia comprehend the Modern Greek language from a psycholinguistic perspective, up to level B1 of the Common European Framework of Reference for Languages (CEFR), based on a three-month course and two exams. The conclusions show that adult learners, as opposed to children, are mature, educated, and autonomous enough to effectively comprehend the foreign language material they are taught. Some of them, however, do not reach even the A1 level of comprehension in the skills of speaking and reading, specifically regarding the past simple tense, irregular verbs, and translation from the foreign language to their mother tongue.